The Study of Water Quantity and Quality (Case Study: Gajahwong Watershed) - Sukma Sayono Putro (Journal of the Civil Engineering Forum, 2016)
Gajahwong River is one of the nine rivers in the Special Region of Yogyakarta Province. During dry season, its water quantity has been decreasing so the water flow is insufficient to dilute the pollutant from sewage and affecting the water quality. Some pollutant parameters that have exceeded the quality standard in the Gajahwong river are including BOD, COD, TSS, phosphates, and total coliform. The study is expected to show the relationship between the water quantity and water pollution parameters and how to mitigate it. Water availability at the river was analyzed by using Mock model and the result was presented in flow duration curve. Climate data including rainfall for 12 years period from 2001 to 2012 were collected.Thecondition of river water quality was analyzed using Pollution Index Method. Results show that dependable flow at 80% probability was 0.80 m3/s. Water quality conditions in the Gajahwong River from upstream to downstream have declined at moderately polluted level. During 2007 to 2012 the level of TDS, TSS, DO, COD, detergents, oils, and fats, and fecal coliform has decreased. The concentration of water quality parameters was increased like BOD, phosphate, and total coliform that causing polluted water. The concentration of TSS, BOD, COD, phosphates, detergents, oils and fats, fecal coliform, and total coliform exceeds the threshold of water quality standards class II.